Genetic Structure of the ‘roble belloto’ Quercus skinneri (Fagaceae) in El Salvador (UNED Research Journal, 2025)
Introduction: In El Salvador, Quercus skinneri Benth. is restricted to high-altitude temperate areas. The lack of genetic studies limits conservation decision-making, despite the importance of genetic diversity in these forests. Objective: To determine the genetic variability and structure of Q. skinneri populations in three localities of El Salvador. Methods: Samples were collected between July and December 2020. We assessed the genetic variability of the tree by collecting leaves from ten individuals per locality, and sequencing and analyzing a total of 19 individuals using two DNA barcode regions: a nuclear region (ITS2) and a plastid region (trnH-psbA). Based on aligned sequences, we calculated genetic diversity indices, population structure, isolation by distance, and phylogeny. Results: Genetic diversity was higher in ITS2 (π = 0.01576; Hd = 0,90643; h = 10) than in trnH-psbA (π = 0,00519; Hd = 0,48538; h = 3). Both regions showed populational structure, with the San Vicente Volcano population clearly differentiated (FST = 0,79972–1) from the others, as reflected in haplotype maps and phylogenetic trees. Conclusion: ITS2 and trnH-psbA differed in their ability to detect genetic variability in Q. skinneri. Both revealed populational structure, notably the differentiation of San Vicente Volcano, suggesting distinct genetic lineages. Introduction: In El Salvador, Quercus skinneri Benth. is restricted to high-altitude temperate areas. The lack of genetic studies limits conservation decision-making, despite the importance of genetic diversity in these forests. Objective: To determine the genetic variability and structure of Q. skinneri populations in three localities of El Salvador. Methods: Samples were collected between July and December 2020. We assessed the genetic variability of the tree by collecting leaves from ten individuals per locality, and sequencing and analyzing a total of 19 individuals using two DNA barcode regions: a nuclear region (ITS2) and a plastid region (trnH-psbA). Based on aligned sequences, we calculated genetic diversity indices, population structure, isolation by distance, and phylogeny. Results: Genetic diversity was higher in ITS2 (π = 0.01576; Hd = 0,90643; h = 10) than in trnH-psbA (π = 0,00519; Hd = 0,48538; h = 3). Both regions showed populational structure, with the San Vicente Volcano population clearly differentiated (FST = 0,79972–1) from the others, as reflected in haplotype maps and phylogenetic trees. Conclusion: ITS2 and trnH-psbA differed in their ability to detect genetic variability in Q. skinneri. Both revealed populational structure, notably the differentiation of San Vicente Volcano, suggesting distinct genetic lineages.
Keywords: genetic diversity; phylogeny; oak forests; genetic differentiation